Implementasi Pendidikan Demokrasi Melalui Pembelajaran Pendidikan Kewarganegaraan Untuk Membentuk Warga Negara Bertanggung Jawab - Ginanjar, Heri; Septiana, Tina (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This research is motivated by: (1) The occurrence of deterioration of the learning process that led to the Civics students are less concentrated in the learning process. (2). The tendency of educators who teach science merely poured without a change in attitude and behavior of students. (3). Citizenship Education learning model of creativity among junior high school teachers are still less active, creative and innovative. (4). Education claims that democracy through civic education that teaches covers the development of civic intelligence, civic participation and civic responsibility. Based on that, the researchers conducted a study entitled "Implementation of Democracy Through Education Learning Civics To Establish Responsible Citizen" is done in MTs Cisaruagirang Sukabumi. The problems that were analyzed were: (1). Packaging democratic education through learning Citizenship Education in MTs Cisaruagirang Sukabumi. (2). Habituation democratic education and attitudes of students in environmental responsibility MTs Cisaruagirang Sukabumi. (3). The method can be used in education Citizenship Education Learning democracy through attitudes to realize the responsibility of the students in MTs Cisaruagirang Sukabumi. (4). The factors that support and hinder the education process to form a democratic attitude in the student's responsibility MTs Cisaruagirang Sukabumi. (5) The role and efforts in doing the school and the school committee habituation democratic education through Citizenship Education learning to form responsible citizens. To answer these questions used data on democratic education process undertaken during the process of learning and school activities through observation, interviews, documentary studies, and literature. The approach used in this study is a qualitative approach to the case study method with a form of exploratory aimed to reveal and understand the circumstances that occur in the field, through the implementation of democratic education is expected to democratic attitudes of students so that the learning process is active, creative and innovative, and fun. The results of the study of democracy education through Citizenship Education learning to form responsible citizens in MTs Cisaruagirang Sukabumi generate active student learning, creative and innovative to make the grade as a laboratory of democracy, the educational content of democracy is equal rights and obligations in school. The emergence of active students in school attitudes make the students are always active in school activities and are taught to always be responsible for the act of doing as a form of education shape the success of the democratic process that is responsible. Recommendations of this study include: (1). Education learning democracy through civic education can be used as an alternative solution in the growing involvement of the student in the classroom or in the school environment. (2). Required cooperation between teachers, the school and the entire school community to be able to carry out democratic education, because it is associated with creativity and liveliness school teacher in the formation of attitudes the student's responsibility.